Utilização de um modelo como estímulo composto discriminativo na aquisição do comportamento verbal de uma criança autista - M.Bandeira (1994)
This research compared three terapeutic interventions for developing verbal behavior in a 17 years old adolescent girl presenting interruption of speech since she was 2 1/2 years old: positive reinforcement, modeling and pairing of discriminative stimuli. A single case experimental design was used. A-B, adapted for comparing the three procedures. The results show no increase in the frequency of verbal behavior during the first two procedures, but only when the third procedure was introduced. We obtained 100% of correct echoic responses after 19 sessions and 100% of corret taet responses after 33 sesseions. Fading out of the prompts was necessary for attaining the target behaviors. This research shows that when the subject's ecolalic behavior is limited to only one model, it is necessáry to proceed in pairing the model and the terapeutic stimuli together in order to obtain a transfer of verbal stimulus control.